External Treatment With Chinese Herbal Medicine for Chemotherapy-Induced Peripheral Neuropathy: A Systematic Review and Meta-Analysis - Li, Quan-yao; Cai, Fei-hong; Lu, Ying; Liu, Hui; Wang, Xiao; Li, Fan-lian; Shi, Jun (Frontiers in Pharmacology, 2022)
Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a common adverse reaction of chemotherapy. Many studies have confirmed that traditional Chinese medicine (TCM) has unique advantages for treating CIPN. However, there is no standard TCM prescription in clinical practice or objective outcome index, and similar efficacy varies. Therefore, in this study, a systematic review of randomized controlled trials (RCTs) was performed to evaluate the clinical efficacy of external treatment with Chinese herbal medicine (CHM) for CIPN. This analysis provides evidence-based medical support for the use of CHM for external treatment of CIPN. Methods: Relevant RCTs assessing CHM external treatment of CIPN were searched in nine electronic databases, including the China National Knowledge Infrastructure Database, China Biology Medicine Disc, China Science and Technology Journal Database, Wanfang Database, PubMed, Cochrane Library, MEDLINE, Web of Science, and OVID, from inception to July 2021. A meta-analysis was performed on these studies using RevMan5.3 software. Results: Based on the inclusion and exclusion criteria, 33 clinical studies were included, while 1,354 studies were screened out. There were 2,356 patients in total, including 1,208 in the treatment group and 1,148 in the control group. In the treatment group, peripheral neurotoxicity rate, total effect rate, KPS score, TCM syndrome score and efficacy, pain NRS score, and pain relief rate were significantly improved compared with those of the control group (p < 0.01). Furthermore, the peroneal and median nerve conduction velocities were also improved compared with those in the control group (p < 0.05). By creating a funnel plot for the incidence of peripheral neurotoxicity and the total effect rate, we showed that the left and right sides were symmetrical, and that the publication bias was low. Conclusion: CHM external treatment was found to be an effective method for treating CIPN as it significantly improved clinical symptoms and quality of life in patients with CIPN. Clinical Trial Registration: identifier ChiCTR1900024617